2017
DOI: 10.1063/1.5003218
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring magnetostriction with various directions for directional solidification Fe82Ga15Al3 alloy by magnetic field heat treatment

Abstract: The magnetostriction of the Fe82Ga15Al3 alloy, along the length and width, can be tailored by applying a magnetic field heat treatment. In this work, the Fe82Ga15Al3 sheet was cut from the directional solidified Fe82Ga15Al3 alloy with the ⟨100⟩ preferred orientation and was annealed at 720 °C for 30 min under a magnetic field of 800 Oe along the length direction with a heating and cooling rate of 100 °C/min. The magnetostrictive properties along the length and width directions were modified to λ// = 7 ppm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, SMF has extensive applications in the solid-solid phase transformations to alter the transformation temperatures, the phase constitutions and selection, the phase morphology and disorder-order transition [29,30]. Moreover, magnetic field annealing has been confirmed to enhance the performances of some magnetostrictive materials [31,32]. It is the purpose of the present work, to compare the effects of SMFs to magnetostriction of Fe-Ga alloys in solidifying and/or annealing processing.…”
mentioning
confidence: 97%
“…Therefore, SMF has extensive applications in the solid-solid phase transformations to alter the transformation temperatures, the phase constitutions and selection, the phase morphology and disorder-order transition [29,30]. Moreover, magnetic field annealing has been confirmed to enhance the performances of some magnetostrictive materials [31,32]. It is the purpose of the present work, to compare the effects of SMFs to magnetostriction of Fe-Ga alloys in solidifying and/or annealing processing.…”
mentioning
confidence: 97%
“…Bai et al demonstrated a series of stripe or maze domain structures in galfenol alloys with a size of a few microns [33,34]. Many other authors [35][36][37][38][39][40][41][42][43][44] have reported similar structures. These observations account for the bulk of the literature on magnetic domains in galfenol.…”
Section: Domain Structures In Galfenolmentioning
confidence: 92%